2013
DOI: 10.1080/15389588.2013.790538
|View full text |Cite
|
Sign up to set email alerts
|

Proposal for a Frontal Impact and Compatibility Assessment Approach Based on the European FIMCAR Project

Abstract: By adding a full-width test to the current ODB test it is possible to better address the issues of structural misalignment and injuries resulting from high acceleration accidents as observed in the current fleet. The estimated benefit ranges from a 5 to 12 percent reduction of fatalities and serious injuries resulting from frontal impact accidents. By using a deformable element in the full-width test, the test conditions are more representative of real-world situations with respect to acceleration pulse, restr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…For both sides of the area, (7) Where, the collision force of each line of TCi target is calculated as follows…”
Section: Hsi Indexmentioning
confidence: 99%
See 1 more Smart Citation
“…For both sides of the area, (7) Where, the collision force of each line of TCi target is calculated as follows…”
Section: Hsi Indexmentioning
confidence: 99%
“…The MPDB test scheme is published in the EURO-NCAP 2020-2025 road map, and it is planned to include vehicle compatibility as a sub-item in the evaluation scoring system [5][6]; Japan also actively participates in vehicle collision compatibility research, and has conducted extensive technical exchanges with Europe and America: it is suggested that the combination test of full frontal crash test and second energy-absorbing structure (SEAS) be used for evaluation. When the load on SEAS reaches 100KN, the displacement of SEAS must be controlled within 400mm [7]. At the moment, China's collision regulations and C-NCAP test methods are primarily aimed at protecting vehicle occupants, but no research on its own aggression has been conducted.…”
Section: Introductionmentioning
confidence: 99%
“…Source: Royal Malaysia Police Traffic Branch, Bukit Aman Global road accident studies indicate that the severity of injuries due to frontal impact is the most relevant factor pertaining to car occupants' deaths (Johannsen et al, 2013). A frontimpact car accident (or normally referred to as a head-on collision) occurs when the front-end of two vehicles collide with each other.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, numerous proposals have been made (e.g. Edwards et al 2012;Johannsen et al 2013;Johannsen and Thomson 2016). However, C2C collisions, which are the main focus of compatibility, are a complicated phenomenon because the combinations of vehicle models and collision conditions are quite diverse.…”
Section: Introductionmentioning
confidence: 99%